A Flexible Wearable Antenna with Annular Solar Eclipse Structure for ISM/WLAN/WIMAX/Bluetooth Applications - Zhen Yu; Runzhi Sun; Guodong Zhang; Ruirong Niu; Xiaoying Ran; Ziheng Lin (International Journal of Antennas and Propagation)
This paper proposes a wearable flexible dual-band antenna that covers the 2.34–2.68 GHz and 4.05–5.26 GHz frequency bands. This antenna employs a novel nested imitation annular solar eclipse structure, where the main radiator is a gradually widening loop, and another loop is coupled inside the radiator. The antenna, with overall dimensions of 40∗32∗0.3 mm³, utilizes polyimide as the dielectric material. The gain, efficiency, and cross-polarization of the antenna were tested using a microwave anechoic chamber. The antenna achieves a maximum gain of 6 dBi and a maximum efficiency of 79.6%. We tested the SAR of the antenna at 10 mm from the human body, which was significantly below the international standard of 2.0 W/kg. The flexible antenna presented in this paper exhibits a broad low-frequency bandwidth, enabling coverage of various communication bands such as ISM, WLAN, WIMAX, and Bluetooth. The antenna delivers satisfactory simulation and measurement results while meeting the requirements of minimizing radiation exposure to the human body.